Mathematical reasoning writing and proof - Sundstrom, Theodore A. (Prentice Hall, 2003)
Designed as a text for a first course in the college mathematics curriculum that focuses on the formal development of mathematics, this book explains how to read and understand mathematical definitions and proofs, and how to construct and write mathematical proofs. Emphasis is on writing mathematical exposition, with guidelines for writing proofs incorporated throughout the text. Learning features include preview activities that prepare students to participate in classroom discussion and activities for in-class group work. Coverage encompasses logical reasoning, constructing and writing proofs, set theoy, mathematical induction, functions, and topics in number theory and set theory